Branding and National Identity: The Analysis of Turkey: Discover The Potential Campaign - (:unkn) unknown (AHMET YESEVI UNIV, 2017)
Nation branding has been an important communication strategy for the governments all around the world in the 21st century. Functioning as a vehicle for conveying messages regarding the nations identity to internal and external audiences, nations are imaged and communicated to the wider audiences as brands. As a regional power with political, historical, cultural and economic significance, Turkey is one of the countries attempting at nation branding in recent years. In this regard, this article analyzes Turkeys nation branding campaign initiated in 2015, under the slogan Turkey: Discover the Potential. With the analysis of elements constituting brand identity, logo and advertisements,this article aims to point out the textual and visual ways in which Turkey is branded with a particular national identity for internal and global audiences.
Keywords: Advertising; branding; brand identity; nation branding; national identity; Turkey; JAPAN